Kelimpahan Ubur-ubur (Aurelia Aurita L.) Diperairan pantai batu kalang Tarusan,Kabupaten Pesisir Selatan,Sumatera barat. - Rahmah, Firdawati Febrina; Zakaria, Indra Junaidi (Universitas Riau, 2017)
Jellyfish are marine life that abundant in the waters of Indonesia, however its considered harmful and waste for fishermen because of its stinging cells,so it has not been exploited optimally by the community. The purpose of this research is to determine the abundance of jellyfish (Aurelia aurita L.) in Coastal Waters of Batu Kalang, Tarusan, Pesisir Selatan regency, West Sumatra. This study was done in March, May and October 2016 with a survey method and the distribution of two locations: the locations I is 50 m from the beach and locations 2 is 150 m from the beach then divided into 6 sampling points. The results are in March obtained A. auritaL. 27 ind /20 efforts, in May 76 ind /20 efforts and in October 15 ind/20 effort, from 3 months of observation A.aurita L. more found in location 1 than location 2. In March, A. aurita L. obtained in the phase Ephyra while in May and October obtained in a phase medusa. The average value of the diameter of the body of A. aurita L. in March was 10.26 cm, 25.80 cm in May and 13.53 cm in October. The relationship between the diameter and weight A. aurita L. is a positive linear, the larger the diameter then the more weight ofA.aurita L. body.